Changes in opioid-related deaths following increased access to opioid substitution treatment - Lisa Andersson; Anders Håkansson; Jonas Berge; Björn Johnson (BMC, 2021)
Abstract Background Opioid-related mortality is high and increasing in the Western world, and interventions aimed at reducing opioid-related deaths represent an important area of study. In Skåne County, Sweden, a patient choice reform resulted in increased access to opioid substitution treatment (OST). In addition, a gradual shift towards less restrictive terms for exclusion from OST has been implemented. The aim of this study was to assess the impact of these policy changes on opioid-related deaths. Methods Detailed data on opioid-related deaths in Skåne during the 2 years prior to and following the policy change were obtained from forensic records and from health care services. Data on overdose deaths for Skåne and the rest of Sweden were obtained using publicly available national register data. Time periods were used as the predictor for opioid-related deaths in the forensic data. The national level data were used in a natural experiment design in which rates of overdose deaths were compared between Skåne and the rest of Sweden before and after the intervention. Results There was no significant difference in the number of deaths in Skåne between the data collection periods (RR: 1.18 95% CI:0.89-1.57, p= 0.251). The proportion of deaths among patients enrolled in OST increased between the two periods (2.61, 1.12-6.10, p= 0.026). There was no change in deaths related to methadone or buprenorphine in relation to deaths due to the other opioids included in the study (0.92, 0.51-1.63, p= 0.764). An analysis of national mortality data showed an annual relative decrease in unintentional drug deaths in Skåne compared to the rest of Sweden following the onset of the reform (0.90, 0.84-0,97, p= 0.004). Conclusions Opioid-related deaths, as assessed using forensic data, has not changed significantly in Skåne following a change to lower-threshold OST. By contrast, national level data indicate that the policy change has been associated with decreased overdose deaths. The discrepancy between these results highlights the need for more research to elucidate this issue. The result that more patients die during ongoing OST following an increase in access to treatment underlines the need for further preventive interventions within the OST treatment setting.